Sistem Pakar Diagnosa Penyakit Awal Tuberkulosis (TB) Menggunakan Metode Dempster Shafer - Syurah A Furqany; Najirah Umar; Rahmaniar, Rahmaniar (Ikatan Ahli Informatika Indonesia, 2023)
Tuberculosis (TB) is one of the most dangerous diseases in Indonesia. The risk of death is caused by the presence of drug resistant bacteria. Treatment lasts quite a long time at least 6 months, after the doctor evaluate whether to continue or stop, because the long treatment often causes patients to abandon treatment or take treatment irregularly, it's very deadly makes the germs become immune so that they cannot be treated. The increasing number of tuberculosis patients in Indonesia is caused by the large number of poor people who lead unhealthy lifestyles and the lack of information provided to the public about tuberculosis.To overcome the existing problems and to increase the knowledge of ordinary people about Tuberculosis, an expert system is made whose knowledge base taken directly from the expertise of certain people transferred in a computer.This TB diagnosis expert system has been successfully built by applying the dempster-shafer method and can provide disease information as well as prevention and treatment.After manual calculations on the Dempster-Shafer method, a confidence level of 0.57 or 50% of the calculation results in the case of Lung TB disease was obtained.